Identifikasi Faktor Dominan Penyebab Kerentanan Bangunan Di Daerah Rawan Gempa, Provinsi Sumatera Barat - Zulfiar, M Heri; Tamin, Tamin; Pribadi, Krishna S; Irwan, Iswandi (Semesta Teknika, 2014)
West Sumatra is one of the province in Indonesia owning high earthquake risk. Disaster data in last one decade show the existence of occurence of earthquake generating damage of building in gross. This matter indicate that building in West Sumatra susceptance ofÂ  earthquake. One of the building susceptance is management of construction which disagree with needed conditions, law and regulation goodness which in rough, and also execution of imprecise development, imprecise build, either from planning facet and scheme, execution and observation, and also from exploiting facet and treatment. It can make infrastructure and building susceptance of disaster. When disaster happened, construction sector product becoming not function, it will generate disaster victim, or generate big loss, because destruction of other infrastructure or building. Research identify dominant factor is building susceptance represent the part of research of dissertation in the effort to less of building susceptance ( mitigation) to earthquake, by :1) sekunder data analysis of building effect of earthquake 2) perception of building characteristic and practices build 3) interview to some construction expert and earthquake. Research location in six sub-province / disaster gristle town that is; Padang city, Padang Panjang city, sub province ofÂ  South Pesisir, sub province of Tanah Datar, sub province of Pariaman and west Pasaman. Research Object at building with floor lower and confined of un-confined masonry. To know potency cause of susceptance by triangulation and sintesis among the data, fact and opinion of expert. Result of research indicate that there are 23,6 % building residing in less condition or did not maintained. To be evaluated from building form, there are 11,1% less up to standard building hold up earthquake that is having regularity of vertical form and horizontal. Pursuant to characteristic usage of brick wall with building structure there are 40,8 % having structure system susceptance of earthquake that is using inappropriate practical log and column.